PEMANFAATAN KOMPOSTER SEDERHANA SEBAGAI SOLUSI ALTERNATIF MENGATASI SAMPAH DI PERUMAHANPODOSUGIH KOTA PEKALONGAN - Jaelani, Ahmad; Purwanti, Henny Indah; Aziz, Muhammad Rifqi (Program Kreativitas Mahasiswa - Pengabdian Kepada Masyarakat, 2013)
Population growth, changes inconsumption patterns and life style of the people have increased the amount of waste,type, waste characteristics and diversityas well as contributinggreatly to the quantity and quality of waste generated. According to the fact, itâs needed waste processing technique well, to give a good environtment. By Student Creativity Program that focusses in Society Service Program, itâs offered waste processing technique in Podosugih, Pekaolongan City, to help people in waste reduction especially organic waste, so they can minimaze the waste and maximase in recycling, by using simple composer. The methods of program are lecture, discussion, demonstrate, and assistance method. The achievement reached of program are people become more creative, and know how to recycle the waste using a simple composter independently. So, the environtment can be clean and healhty. Beside, they can produce organic liquid fertilizer product.